The Role of Support From Supervisors and Co-Workers on Financial Service Marketing Agents’ Performance in The Aspects of Work Motivation and Satisfaction - Rafiqah Saputri Abdullatif; Rina Anindita (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
The barrier between employees, or the barrier between employees and supervisors in the marketing agency context has been a serious issue that causes detrimental consequences, such as demotivation, degrading productivity, and reduced work performance among employees. The importance of the supervisor and co-worker support has now become a crucial topic, as it is proven to be advantageous for organizations. This research was conducted using questionnaires back in December 2019 until January 2020, in which the respondents consisted of 230 marketing agencies of financial services in DKI Jakarta. The data was analyzed using Structural Equation Model (SEM). There are some significant results in this research. Firstly, there is an association between supervisor support and employee motivation. Secondly, there is an association between co-worker support and work motivation. Next, there is an association between co-worker support and job satisfaction. Fourth, there is an association between work motivation and job satisfaction. Moreover, there is an association between work motivation and employee performance. Lastly, there is an association between job satisfaction and employee performance. However, there is no significant association between supervisor support and job satisfaction.